2009
DOI: 10.2478/s11535-009-0051-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in exon 7 of the endothelial nitric oxide synthase gene is associated with low incidence of microvascular damage in type 1 diabetic neuropathy

Abstract: Microvascular complications associated with type 1 diabetes mellitus (T1DM) are caused in part by endothelial dysfunction. We aimed to determine the association between polymorphisms in endothelial nitric oxide synthase (eNOS) gene (894G>T, 4ab) and T1DM-associated microvascular disorders, and the roles of nitrite/nitrate products (NOx) and low molecular weight-AGEs (LMW-AGEs) levels in this relationship. We carried out a case-control study (328 subjects) and determined genotypes by PCR. The rare-type TT of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Recent reports and our studies showed that there were no relationships between 4b/4a variant of NOS3 and DR or other microangiopathic complications. Similar results for rs1799983 in relation with DR were also reported (Heltianu et al, 2009;Mamulakis et al, 2009). In a metaanalysis of genetic association studies for DR in T1DM, from the three NOS3 polymorphisms (rs1799983, rs3138808 and rs41322052) included in the sub analysis for Caucasian subjects, none of them were found to be significantly associated with any form of DN (Abhary et al, 2009a) The progression of renal disease was associated with the NOS3 rs2070744 variant (Freedman et al, 2007;Zanchi et al, 2000), a result confirm recently by meta-analysis (Mooyaart et al, 2011;Ned et al, 2010).…”
Section: Nos3 Genesupporting
confidence: 86%
See 3 more Smart Citations
“…Recent reports and our studies showed that there were no relationships between 4b/4a variant of NOS3 and DR or other microangiopathic complications. Similar results for rs1799983 in relation with DR were also reported (Heltianu et al, 2009;Mamulakis et al, 2009). In a metaanalysis of genetic association studies for DR in T1DM, from the three NOS3 polymorphisms (rs1799983, rs3138808 and rs41322052) included in the sub analysis for Caucasian subjects, none of them were found to be significantly associated with any form of DN (Abhary et al, 2009a) The progression of renal disease was associated with the NOS3 rs2070744 variant (Freedman et al, 2007;Zanchi et al, 2000), a result confirm recently by meta-analysis (Mooyaart et al, 2011;Ned et al, 2010).…”
Section: Nos3 Genesupporting
confidence: 86%
“…It was reported that this variant changes the NOS3 protein sequence, probable resulting an alteration of enzyme activity (Costacou et al, 2006), and control the NOS3 intracellular distribution interacting with proteins of degradating process (Brouet et al, 2001). From many polymorphisms of the NOS3 gene some of them are associated with the development of diabetic microvascular complications while others indicated their protective role (Freedman et al, 2007;Heltianu et al, 2009). A recent study of rs2070744 in Caucasian T1DM reported a positive association with diabetes per se as well as DR and two possible explanations were found; either NOS3 is a candidate gene for the microvascular disease, or there is a linkage disequilibrium between NOS3 and the neighbouring genes.…”
Section: Nos3 Genementioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Nevertheless, the precise mechanisms by which hyperglycemia induce pathological outcomes and the molecular nature of its downstream effectors is still a debatable issue.…”
Section: Introductionmentioning
confidence: 99%